Net-zooplankton abundance and biomass from Annaba Bay (SW Mediterranean Sea) under estuarine influences - OUNISSI, M.; LASKRI, H.; KHÉLIFI-TOUHAMI, M. (Mediterranean Marine Science, 2016)
<!–[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]–> Zooplankton samples were collected in Annaba Bay (Algeria) from January 2009-March 2011 at three coastal sites differently affected by estuarine plumes and external currents. Aim of this survey was to analyze zooplankton composition, abundance and biomass<span style="font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: AdvOT863180fb; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;" lang="EN-US"> and compare the results with previous studies to reveal possible populations and environmental changes. The mean zooplankton abundance varied between 1,200-6,000 ind. m-3 and biomass 6.70-25.70 mg DW m-3, according to the site. Copepods constituted the main fraction of zooplankton community, and Oithona similis and Paracalanus indicus successively dominated during autumn-winter and spring-summer. The dinoflagellate N<span style="font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: AdvOT863180fb; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;" lang="EN-US">octiluca scintillans <span style="font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: AdvOT863180fb; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;" lang="EN-US">was one of the major zooplankton components, and developed high numbers during February-April, becoming common in neritic and coastal regions.<span style="font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: AdvTT5843c571; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;" lang="EN-US"> The singularity of the zooplankton from Annaba Bay is the prevalence of P. indicus throughout the entire bay and the decrease in Acartia discaudata and A. clausi (with respect to previous years), possibly replaced by A. negligens. Additionally, Oithona nana abundance markedly decreased with the large development of O. similis. Annaba Bay also differs from other similar Mediterranean coastal areas by the large development of Centropages ponticus populations during the warm period. Among the identified copepod species, the alien species Pseudodiaptomus australiensis and P. arabicus are reported for the first time in the Mediterranean Sea. The occurrence of copepodid V stages of P. australiensis suggests that this species survives and reproduces in Annaba Bay, but so far without developing an abundant population. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Κανονικός πίνακας"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>